A framework of innovative learning for skill development in complex operational tasks - Hou, L.; Chi, Hung-Lin; Tarng, W.; Chai, J.; Panuwatwanich, K.; Wang, X. (Elsevier BV, 2017)
© 2017 Elsevier B.V. As today's oil and gas projects are becoming larger and more complex, project managers are constantly faced with a number of concerns about schedules, budgets, productivity and safety. Operating an oil and gas facility is a process where workers refer to technical specifications to obtain the right information, identify the components, and then make a decision as to the adjustment or correctness. This entire process is iterative and triggers a learning process which may lead to improved proficiency as the cycle is repeated. The inability to find the right information or sequence within a cycle can contribute to efficiency losses. Jobsite training offered by qualified organisations and associations for the oil and gas industry is very limited, and the relevant training facilities and centres that have been established or considered in the construction agenda are far from sufficient to the growing standard of operators and industry expansion. This paper, underpinned by advanced innovative visualisation technologies, proposes a framework to improve efficiency and expedite the process of developing the complex procedural skills in operating and maintaining oil and gas facilities, through identifying scientific principles of enabling complex procedural learning approaches, developing proficiency-based learning approaches and corresponding learning curricula, and appraising learning outcomes according to developed skillset taxonomy. The proposed framework is tested under the development of an innovative and immersive Augmented Reality/Virtual Reality training system, which reveals significantly pragmatic benefits in terms of boosting up workforce productivity while bringing down rework. It is also demonstrated that embedding paradigms of transformative learning process while pedagogically adopting Information Communication Technologies (ICT) in curricula development and assessment regimes can help the sector significantly improve workforce safety.